Spectral Analysis of Surface Wave for Empirical Elastic Design of Anchored Foundations - S. E. Chen; C. K. Ong (Advances in Civil Engineering)
Helical anchors are vital support components for power transmission lines. Failure of a single anchor can lead to the loss of an entire transmission line structure which results in the loss of power for downstream community. Despite being important, it is not practical to use conventional borehole method of subsurface exploration, which is labor intensive and costly, for estimating soil properties and anchor holding capacity. This paper describes the use of an empirical and elasticity-based design technique coupled with the spectral analysis of surface wave (SASW) technique to provide subsurface information for anchor foundation designs. Based on small-strain wave propagation, SASW determines shear wave velocity profile which is then correlated to anchor holding capacity. A pilot project involving over 400 anchor installations has been performed and demonstrated that such technique is reliable and can be implemented into transmission line structure designs.